Spatial Patterns and Correlates of Lower Respiratory Tract Illnesses in Children from Drakenstein, Western Cape - Bhenxa, Namhla (Department of Public Health and Family Medicine, 2023)
Background: Lower respiratory tract infections (LRTIs) in children under 5 years of age are a major public health concern globally with high proportions of cases occurring in low- and middle-income countries. However, little is known about the spatial variation of LRTIs especially in developing countries such as South Africa. This study aimed to explore and map the spatial dependence and clustering of childhood pneumonia and wheeze and to identify factors associated with these diseases in two communities of the Western Cape province in South Africa. Methods: This analysis used case-control data from the Drakenstein Child Health Study. Cases were children who developed pneumonia or wheeze, and controls were incidence density matched on date of birth, age, and enrolment site. Smooth maps were created using Kernel density estimation and cluster analysis was performed using Ripley's K function and Kullddorf spatial scan statistics. Finally, generalized additive models were used to identify socio-demographic factors associated with pneumonia and wheeze. Results: A total of 947 children were included in analysis, with 406 cases of wheeze and 466 cases of pneumonia. Overall, cases and controls had a similar spatial concentration, although there was some variation in the density of wheezing cases in comparison to controls. In particular, there was evidence of a non-random difference in the distribution between cases and controls, and cases of wheeze were significantly more concentrated the TC Newman area than expected. Those who developed pneumonia and wheeze were more likely to be males as compared to females (both p<0.05). There were no statistically significant association between socioeconomic status, ethnicity, education, breastfeeding practices and maternal smoking (all p>0.05). Conclusions: This study revealed a significant clustering of wheeze in TC Newman, which may be attributable to socio-demographic differences between communities, while pneumonia was spatially dispersed across the study areas. These findings suggest that focused public health interventions are needed to reduce the incidence of LRTIs in the area of TC Newman specifically.